EFL teachers’ strategies to accommodate students’ learning styles in distance learning and their challenges - Geby Devtiana Maryono; Nenden Sri Lengkanawati (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2022)
COVID-19 outbreak has shifted the learning and teaching process into distance learning. This situation has challenged the teachers, as the experts suggest, to include learning styles in teaching planning to help students. This study aims to examine how EFL teachers accommodate students' learning styles in distance learning to help students comprehend and acquire language and the teachers' challenges in accommodating students' learning styles. It employed a phenomenological qualitative method using interviews and observation to gain the data. The study found that EFL teachers used various online platforms, created/adjusted materials, and gave many assessment forms to accommodate students' learning styles in distance learning. However, it was impossible to accommodate every learning style in the classroom because of several challenges such as connection/technical problems, teachers' workload, many students in the class, and students' lack of motivation. It can be concluded that accommodating students' learning styles is more challenging in distance learning than in face-to-face classrooms. The study results are useful as a reference in the issue of learning styles to evaluate the practices of accommodating students' learning styles in distance learning.